Genomic-assisted characterisation of Pseudomonas sp. strain Pf4, a potential biocontrol agent in hydroponics. Issue 8 (3rd August 2017) - Moruzzi, Serena; Firrao, Giuseppe; Polano, Cesare; Borselli, Stefano; Loschi, Alberto; Ermacora, Paolo; Loi, Nazia; Martini, Marta
ABSTRACT: In an attempt to select potential biocontrol agents against Pythium spp. and Rhizoctonia spp. root pathogens for use in soilless systems, 12 promising bacteria were selected for further investigations. Sequence analysis of the 16S rRNA gene revealed that three strains belonged to the genus Enterobacter, whereas nine strains belonged to the genus Pseudomonas . In in vitro assays, one strain of Pseudomonas sp., Pf4, closely related to Pseudomonas protegens (formerly Pseudomonas fluorescens ), showed noteworthy antagonistic activity against two strains of Pythium aphanidermatum and two strains of Rhizoctonia solani AG 1-IB, with average inhibition of mycelial growth >80%. Strain Pf4 was used for in vivo treatments on lamb's lettuce against R. solani root rot in small-scale hydroponics. Pf4-treated and untreated plants were daily monitored for symptom development and after two weeks of infection, a significant protective effect of Pf4 against root rot was recorded. The survival and population density of Pf4 on roots were also checked, demonstrating a density above the threshold value of 10 5  CFU g −1 of root required for disease suppression. Known loci for the synthesis of antifungal metabolites, detected using PCR, and draft-genome sequencing of Pf4 demonstrated that Pseudomonas sp. Pf4 has the potential to produce an arsenal of secondary metabolites ( plt, phl, ofa and fit-rzx gene clusters) very similar to that of the well-known biocontrol P. protegens strain Pf-5.